Anthropocene or Anthropobscene?: A reading of the ecological crisis from mainländerian metaphysical observations - Donoso, Claudia (Cosmos and History: The Journal of Natural and Social Philosophy, 2025)
The present paper seeks to account for the spirit of the current geological epoch on the basis of the dialogue between the concept of dump developed by Michael Marder and Philipp Mainländer’s will to die. Specifically, it is proposed that behind the mismatch between our civilizational behavior and ecological urgencies there could be philosophical questions of a metaphysical nature. Perhaps, the history of destruction that civilization has been installing is nothing more than the exemplification of what Mainländer mythopoietized in the law of the weakening of the force present in the universe, now expressed in the form of a collective suicide into the abyss of the dump.